Blake Edwards' the return of the Pink Panther [videorecording (DVD)] - Edwards, Blake, 1922-2010; Edwards, Blake, 1922-2010; Edwards, Blake, 1922-2010; Sellers, Peter, 1925-1980; Plummer, Christopher; Schell, Catherine, 1946-; Lom, Herbert (Artisan Home Entertainment, 1999)
Inspector Clouseau is summoned to recover the world's largest diamond, stolen from a seemingly secure museum, and focuses on an English peer as the most likely suspect.